The Antioxidant Moiety of MitoQ Imparts Minimal Metabolic Effects in Adipose Tissue of High Fat Fed Mice - Bond, Simon T.; Kim, Jisu; Calkin, Anna C.; Drew, Brian G. (Frontiers in Physiology, 2019)
Mitochondrial dysfunction is associated with a diverse array of diseases ranging from dystrophy and heart failure to obesity and hepatosteatosis. One of the major biochemical consequences of impaired mitochondrial function is an accumulation of mitochondrial superoxide, or reactive oxygen species (ROS). Excessive ROS can be detrimental to cellular health and is proposed to underpin many mitochondrial diseases. Accordingly, much research has been committed to understanding ways to therapeutically prevent and reduce ROS accumulation. In white adipose tissue (WAT), ROS is associated with obesity and its subsequent complications, and thus reducing mitochondrial ROS may represent a novel strategy for treating obesity related disorders. One therapeutic approach employed to reduce ROS abundance is the mitochondrial-targeted coenzyme Q (MitoQ), which enables mitochondrial specific delivery of a CoQ10 antioxidant via its triphenylphosphonium bromide (TPP+) cation. Indeed, MitoQ has been successfully shown to accumulate at the outer mitochondrial membrane and prevent ROS accumulation in several tissues in vivo; however, the specific effects of MitoQ on adipose tissue metabolism in vivo have not been studied. Here we demonstrate that mice fed high-fat diet with concomitant administration of MitoQ, exhibit minimal metabolic benefit in adipose tissue. We also demonstrate that both MitoQ and its control agent dTPP+ had significant and equivalent effects on whole-body metabolism, suggesting that the dTPP+ cation rather than the antioxidant moiety, was responsible for these changes. These findings have important implications for future studies using MitoQ and other TPP+ compounds.